2017
DOI: 10.1177/0885066617704390
|View full text |Cite
|
Sign up to set email alerts
|

Remifentanil for Sedation of Children With Traumatic Brain Injury

Abstract: This data suggest that remifentanil is a suitable sedative agent for use in children with TBI. It provides a rapid onset of sedation with recovery that permits reliable and reproducible clinical examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…However, multiple practice survey and intra-analgesic class comparative studies do describe IV opioids as the primary analgesic class used across the spectrum of critically ill pediatric patients (3,5,33,61,62). A variety of IV opioids have been used in this setting including fentanyl, morphine, hydromorphone, and remifentanil (63)(64)(65)(66)(67)(68)(69). Due to lack of active metabolites, fentanyl may be preferred in the setting of renal dysfunction.…”
Section: Pharmacologic Management Of Painmentioning
confidence: 99%
“…However, multiple practice survey and intra-analgesic class comparative studies do describe IV opioids as the primary analgesic class used across the spectrum of critically ill pediatric patients (3,5,33,61,62). A variety of IV opioids have been used in this setting including fentanyl, morphine, hydromorphone, and remifentanil (63)(64)(65)(66)(67)(68)(69). Due to lack of active metabolites, fentanyl may be preferred in the setting of renal dysfunction.…”
Section: Pharmacologic Management Of Painmentioning
confidence: 99%
“…RFT is a p ο tent μ-opioid analgesic with advantages in rapid blood–brain barrier equilibration time over other opioids [ 29 ]. Currently, besides the commonly known acute opioid tolerance and postoperative hyperalgesia that RFT can achieve, people usually make a connection between the use of RFT and rapid deep sedation and pain relief for patients with various injuries [ 30 , 31 ]. Some scholars, albeit with no direct evidence provided by experiments, have taken it plausible that RFT can reduce the risk of acute kidney injury [ 32 ].…”
Section: Cell Culturementioning
confidence: 99%
“…It is important to remember some general rules: the causes of acute sudden coma are most often the intake of various drugs or traumatic brain damage -hemorrhage, trauma or hypoxia; subacute development is usually due to previous therapeutic or neurological conditions, including secondary cerebral edema, occurring around a pre-existing lesion [11,12]. Thus, it can be concluded that the existing etiological classifications of coma are not convenient for use in an intensive care situation and only complicate the choice of the optimal tactics for conducting intensive therapy.…”
mentioning
confidence: 99%